ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KAS DIVIDEN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009 - 2011 (Students' Journal of Economic and Management, 2013)
This study aims to examine the influence of Return On Investment, Cash Ratio, Debt To Total Assets, Earning Per Share of the Cash Dividend on LQ45 companies listed in Indonesia Stock Exchange in 2009-2011.The research was conducted in the Indonesia Stock Exchange in 2009-2011 LQ45 companies. Sampling technique using purposive sampling sampling using certain criteria.Of these criteria, then obtained a sample of 24 companies. Analysis technique used is by using multiple linear regression analysis. Multiple linear regression analysis was used to determine the effect of independent and dependent variables. Whereas in hypothesis testing using the t-test. T-test is used to determine the significance of the influence of an independent variable (X) on the dependent variable (Y) partially.The results prove that the Return on Investment (ROI) and Earning Per Share (EPS) significantly affects Cash Dividend (CD), while for the Cash Ratio (CSR) and Debt To Total Assets (DTA) does not affect the Cash Dividend (CD). Keywords: Cash Dividend, Return on Investment (ROI), Cash Ratio (CR), Debt To Total Assets (DTA), Earning Per Share (EPS).